Coronary Microvascular Dysfunction: An Update - Zaman, Sm Mustafa; Hoque, Harisul; Ahmed, Khurshed; Rahman, Md Mukhlesur; Chowdhury, Msi Tipu; Jamil, Md Abu; Khaled, Md Fakhrul Islam (University Heart Journal, 2020)
Structural and functional abnormalities of the microcirculation can impair myocardial perfusion which is called coronary microvascular dysfunction and the resulting ischemia is known as microvascular ischaemia. Most of the researches have focused on the epicardial coronary arteries while addressing angina pectoris. Although the importance of the coronary microcirculation in maintaining appropriate myocardial perfusion has been recognized for several decades, the substantial morbidity of coronary microvascular dysfunction (CMD) has not been appreciated until recently. It is not possible to diagnose of microvascular angina clinically with the current knowledge. Resting or exercise electrocardiogram is nondiagnostic. Imaging with speckle tracking in echocardiography may reveal focal diastolic and/or systolic dysfunction. Other noninvasive investigations includes, Contrast stress echocardiography, 99Tc-sestamibi imaging, cardiovascular magnetic resonance (CMR),Nuclear magnetic resonance spectroscopy may show some degree of abnormality. Invasive methods like intracoronary adenosine and acetylecholine test may guide us to diagnose CMD. No guideline directed medical therapy is still available for the CMD. Risk factors modification like smoking cessation and weight-loss may improve endothelial dysfunction and CMD. Beta blockers, calcium channel blockers, Angiotensin converting enzyme inhibitors and statin are now used in different clinical condition related to microvascular angina. After these medical treatment patient with microvascular angina have higher risk of MACE compared with people without angina. So, physicians must be aware of this potentially fatal but under recognized clinical entity. University Heart Journal Vol. 16, No. 1, Jan 2020; 43-49